Molecular Dynamics Prediction Verified by Experimental Evaluation of the Solubility of Different Drugs in Poly(decalactone) for the Fabrication of Polymeric Nanoemulsions. Issue 1 (29th November 2021) - Pyrhönen, Jasmin; Bansal, Kuldeep K.; Bhadane, Rajendra; Wilén, Carl-Eric; Salo-Ahen, Outi M. H.; Rosenholm, Jessica M.
Abstract : Nanoemulsions are a rapidly growing drug delivery technology capable of increasing a drug's aqueous solubility and stability. A novel oil‐in‐water nanoemulsion using a polymer, poly(decalactone) (PDL), instead of a conventional oil was recently reported. The amount of drug loading in a polymer‐based formulation is mainly governed by the drug's solubility in the polymer. Thus, herein the power of molecular dynamics simulations (MDS) for the calculation of the Hildebrand solubility parameter to predict PDL–drug miscibility is utilized. The MDS results are subsequently verified by formulating a PDL nanoemulsion with a dispersed droplet size of less than 200 nm by using a block copolymer of PDL (mPEG‐b‐PDL) as a surfactant, with seven different hydrophobic drug molecules. The MDS results are consistent with the experimental findings in terms of increment in the aqueous solubilities of the drugs in PDL nanoemulsion, where celecoxib demonstrated the highest while methotrexate exhibited the lowest solubility increment. Consequently, the reported MDS method can be utilized to predict a drug's solubility/miscibility in PDL to estimate the level of drug loading. The MDS facilitated screening of drugs could consequently emerge as an efficient approach in designing PDL nanoemulsions stabilized by mPEG‐b‐PDL or other similar systems. Abstract : A computational pharmaceutics approach is attempted by utilizing molecular dynamics simulations (MDS) to assess polymer–drug miscibility to predict drug loading capacity of the carrier polymer. The MDS results are experimentally verified by formulating nanoemulsions and micelles with seven different hydrophobic drug molecules. This MDS‐facilitated drug screening could constitute an efficient strategy in designing nanoemulsions for drug delivery.